Efektivitas Pendapatan Usaha Pada Perusahaan Daerah Air Minum (PDAM) Tirta Musi Kota Palembang - Reni Apriani (Jurnal Studi Sosial dan Politik, 2018)
This research is titled Effectiveness of Operating Revenue On Regional Water Company (PDAM) Tirta Musi Palembang. This study was aimed to find out how the operating revenue of PDAM Tirta Musi Palembang, and also to find out factors that inhibiting the operating revenue of PDAM Tirta Musi Palembang. The method used in this research was a qualitative method. The results showed that revenues have not been effective because the target was not achieved and non-water sales revenue was decreased. The input owned by PDAM Tirta Musi Palembang was good. However, PDAM Tirta Musi Palembang still has not done well in utilizing the water. The feedback conducted by PDAM Tirta Musi Palembang was quite good, although not as a whole. There were also 2 inhibiting factor in the operating revenues of PDAM Tirta Musi Palembang, namely: the internal factor s which were the limited human resources and a low level of supervision, and the external factors which were the lack of customer awareness in paying water bills and frauds that occurs in society.